An ultra-sensitive, flexible and transparent gas detection film based on well-ordered flat polypyrrole on single-layered graphene. Issue 5 (18th January 2018) - Yoon, Taeseung; Jun, Jaemoon; Kim, Dong Yeon; Pourasad, Saeed; Shin, Tae Joo; Yu, Seong Uk; Na, Wonjoo; Jang, Jyongsik; Kim, Kwang S.
Abstract : Flat oriented polypyrrole on single-layered graphene is prepared by electrochemical oxidative polymerization to dectect sub-ppb NO2 and NH3 gases. Abstract : Real-time gas sensors that are ultra-sensitive, highly selective, and capable of fast response/recovery are highly in demand for environmental and health monitoring; however, advances in such gas sensors have been limited. Here we report a flexible and transparent sub-ppb gas detection film fabricated by in situ electrochemical oxidative polymerization on single-layer graphene (SLG). As polypyrrole molecules are uniformly formed with flat orientations on SLG, the resulting sensor film exhibits excellent sensitivity and selectivity with nearly perfect reversibility without heat treatment or light irradiation. The sensing mechanism is well explained by molecular interactions between the sensing material and the gas molecular species. The sensor exhibits a detection limit as low as 0.03 ppb NO2 and 0.04 ppb NH3 at room temperature and operates well, even at 70 °C, showing feasibility for wearable applications in high-precision gas sensing.